A before−after assessment of the response of mammals to tourism in a Brazilian national park. Issue 6 (21st November 2022) - Barcelos, Daniele; Vieira, Emerson M.; Pinheiro, Marcell Soares; Ferreira, Guilherme Braga
Abstract: Worldwide, nature-based tourism is becoming more popular and important economically. However, there is still debate regarding its impact on wildlife in protected areas. We conducted a quasi-experimental study to investigate the effects of tourism on the mammal community of Cavernas do Peruaçu National Park, a priority area for conservation in Brazil. We used camera traps to survey tourist and non-tourist trails during 2011–2017, encompassing periods before and after tourism started in the Park. We used four metrics for assessment: species richness, probability of using trails, activity levels and daily activity patterns. After tourism began in the Park there was no significant change in species richness and the probability of using tourist trails either increased or remained stable for five of the six species assessed. The rock cavy Kerodon rupestris was the only species to be displaced from tourist areas and to show reduced overall activity on tourist trails after tourism began. The ocelot Leopardus pardalis showed reduced diurnal activity on tourist trails, an indication of temporal adjustment. Overall, our results show that the initial years of visitation at the Park had limited negative impacts on the target mammal species, supporting the possibility of accommodating tourism activity and effective conservation of wildlife in the region. However, it is essential to continue monitoring in the Park because of the expected growth in tourism and potential time lags in responses of species.